Damage of Rock Mass by Double-Hole Blasting with Slit Charge and Development of Stress Wave under High In Situ Stress. (24th January 2022) - Zhang, Jianyu; Liu, Zegong; Fu, Shigui; Qiao, Guodong
Abstract : To study the influence of high ground stress on crack propagation and stress propagation during deep rock blasting, a theoretical model of blasting stress wave propagation and rock damage under in situ stress conditions is developed. The implicit-display coupling method of ANSYS/LS-DYNA is used to numerically simulate the double-hole blasting of the slit charge under two-way equal pressure and two-way different pressures. A theoretical analysis shows that, in blasting under ground stress conditions, at the near end of the blasting source, the loading stress does not increase sufficiently upon unloading, and the stress wave peak value decreases with the increase in ground stress, while the opposite behavior is obtained at the far end of the blasting source. Under the two-way isostatic condition, the crack that develops at 45° deviates from the principal stress direction. Under the condition of two-way different pressures, the crack develops in the direction of θ ( θ = arctan ( σ x / σ y )) with the principal stress angle. The numerical results under the two-way equal pressure conditions show that a higher ground stress leads to a larger suppression of the blasting effect. When the ground stress is smaller, the slit charge cannot be effectively suppressed, and the cracks are biased toward the cutting direction. The numerical results under two-way different pressures show that the in situ stress has a significant inhibitory effect on the vertical cracks and that the cracks are more likely to develop in the direction of high stress after blasting. These results provide a reference for directional blasting of deep rock masses.